BEYOND THE HUNDRED ACRE WOOD: POSTHUMANISM IN A. A. MILNE'S WINNIE-THE-POOH - Ayyildiz, Nilay Erdem (Estonian Acad Publishers, 2025)
Children's literature is a field of study that contributes to the evolution of the posthuman. English author A. A. Milne's prominent book, Winnie-the-Pooh (1926), is set in a posthuman space, the Hundred Acre Wood, inhabited by the human character, Christopher Robin and his animal friends in harmony. The book sets a balance between the human and the nonhuman, culture and nature, reason and sensation. The study analyses how Winnie-thePooh exemplifies the exercise of posthumanism in a children's work to enlighten how the boundaries between the human and the nonhuman are blurred, animal agency and nonhuman subjectivity are constructed in the book, and how communication and nonhuman expressivity transgress anthropocentric language and rationalist discourse by adopting a posthuman approach. Thus, the study reveals that Winnie-the-Pooh contributes to the comprehension and exercise of posthumanism through stories for child readers, transgressing the boundaries set by anthropocentricism in the Disney production of the book.
Keywords: posthumanism; anthropocentricism; children's literature; Winnie-the-Pooh; A. A. Milne; the Hundred Acre Wood; animal agency